2003
DOI: 10.1142/s1088424603000185
|View full text |Cite
|
Sign up to set email alerts
|

Dye-sensitized solar cell with the near-infrared sensitization of aluminum phthalocyanine

Abstract: The dye-sensitized solar cell (DSSC) using visible and near-infrared sensitization of nanocrystalline TiO 2 films using a series of four aluminum phthalocyanines was developed and its photoelectrochemical properties were investigated. By using aluminum 2,9,16,23-tetrakis(phenyl-thio)-29H,31H-phthalocyanine chloride adsorbed on a nanocrystalline TiO 2 film electrode, the I SC , V OC , FF , P max and η values were largest compared with the other DSSCs using aluminum phthalocyanines. For all the DSSCs using alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…These transitions are characterized by the Q band in the visible region of the spectrum, which results from ππ * electron transitions from the highest occupied molecular orbitals (HOMO) (a1u and a2u) to the lowest unoccupied molecular orbitals (LUMO), and occurs at about 600-700 nm. The other one is called the B band and can be seen in the 300-400 nm range due to from deeper π HOMO to LUMO energy levels [33]. In this study,…”
Section: Electronic Absorption Spectramentioning
confidence: 88%
“…These transitions are characterized by the Q band in the visible region of the spectrum, which results from ππ * electron transitions from the highest occupied molecular orbitals (HOMO) (a1u and a2u) to the lowest unoccupied molecular orbitals (LUMO), and occurs at about 600-700 nm. The other one is called the B band and can be seen in the 300-400 nm range due to from deeper π HOMO to LUMO energy levels [33]. In this study,…”
Section: Electronic Absorption Spectramentioning
confidence: 88%
“…[28] Besides transition-metal complexes, a range of organic molecules have been explored, with recent examples including coumarin, [29] squaraine, [30] indoline, [31] hemicyanine, [32] and other conjugated donoracceptor organic dyes, [33][34][35][36] and the best efficiency reported was 8 % (see Figure 7 a in Section 2.5). [31] Porphyrin dyes [37,38] and phthalocyanine dyes [39] have also been explored. The dyes used in DSSC technology must conform to a number of essential design requirements in order to function.…”
Section: General Design Of Dyesmentioning
confidence: 99%
“…In another study, myristic acid was employed as a co-adsorbent of aluminium(III) tetraphenoxy phthalocyanine hydroxide for the sensitization of nanocrystalline TiO 2 . 42,43 It was found that the co-adsorbent showed a dramatic decrease in the aggregation of Pc on the nanocrystalline surface and as a result the test cell efficiency was improved. Balaraju et al 44 have used iron tetrasulfonic acid phthalocyanine (Dye 6) sensitizer and the corresponding device has shown an overall conversion efficiency of 4.1% by employing a PEDOT:PSS-coated FTO counter electrode instead of the usual Pt counter electrode and dilute HNO 3 treatment of TiO 2 .…”
Section: Symmetrical Phthalocyanine Sensitizersmentioning
confidence: 99%